MODERN PARADIGMS OF THE INTERNATIONAL ECONOMY: INTEGRATION AND DIVERGENCE - Egamberdi Ostonov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes contemporary paradigms of international economics, focusing on the processes of integration and divergence. It explores the trends of interconnectedness and differentiation among states, regions, and economic systems in the context of globalization. The interplay of international trade, financial markets, and economic policy is examined to assess the economic, social, and political implications of integration and divergence. The study aims to identify pathways toward achieving global economic balance and sustainable development.